2020
DOI: 10.1017/ice.2020.354
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment: Shortage or waste?

Abstract: To the Editor-With the progression of the coronavirus disease 2019 (COVID-19) pandemic, the personal protective equipment (PPE) shortage has been highlighted. 1 The sudden increase in demand for PPE due to the number of COVID-19 cases, misinformation, panic buying, and stockpiling resulted in global shortages. The World Health Organization (WHO) published a guideline for the rational use of PPE for coronavirus disease in healthcare and home-care settings during severe shortages. 2 Despite the importance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 4 publications
3
11
0
Order By: Relevance
“…As the case in many other countries-even with higher socioeconomic status [ 3 , 21 , [29] , [30] , [31] , [32] ], most of our participants (82.4%) complained of shortage in PPE supplies (which showed statistical correlation with noncompliance). During the first wave, Egypt witnessed a serious shortage in gloves and mask [ 33 ] which caused wide-scale discussions in both; the medical community and the media.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…As the case in many other countries-even with higher socioeconomic status [ 3 , 21 , [29] , [30] , [31] , [32] ], most of our participants (82.4%) complained of shortage in PPE supplies (which showed statistical correlation with noncompliance). During the first wave, Egypt witnessed a serious shortage in gloves and mask [ 33 ] which caused wide-scale discussions in both; the medical community and the media.…”
Section: Discussionsupporting
confidence: 67%
“…When IPC practitioners and employers attempted to optimize the use of respirators, they faced the HCWs’ lack of trust and tendency to demand respirators for every encounter. The same issue had also been highlighted in literature [ 21 , 39 , 40 ]. However, the consumption of authentic imported respirators and intensive awareness campaigns organized by all relevant authorities have eventually led to anincrease in HCWs’ awareness.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…1,2 An observational compliance study regarding specific precautions for COVID-19 patients showed that among improper PPE use, 193 of 322 (60.%) were classified as wasteful practices that contributed to the shortage of these products. 3 The lack of gowns has ignited a search for alternative PPE such as coveralls. The World Health Organization (WHO) guideline did not recommend coveralls as alternative PPE.…”
mentioning
confidence: 99%